Gender Transformation in Humanitarian Response: Insight from Northeast Nigeria. Issue 1 (26th May 2022) - Nwoke, Chikezirim C.; Becker, Jennifer; Popovych, Sofiya; Gabriel, Mathew; Cochrane, Logan
Abstract : Within bilateral and multilateral funding circles, there has been a strong and growing emphasis on the importance of understanding and responding to gender inequalities in humanitarian settings. However, given the often-short funding cycles, among other operational challenges, there is limited scope to incorporate interventions that address the root causes and social norms underpinning gender inequalities, or other gender transformative interventions. In the context of the decade-long crisis in the Lake Chad Basin, fuelled by incursions from non-state armed groups (NSAGs), including Boko Haram, and the resultant protracted and chronic humanitarian crisis, this article examines Save the Children's child nutrition programmes in northeast Nigeria. Taking an ethnographic approach focused on volunteer-driven peer support groups (mother-to-mother and father-to-father) that aim to increase knowledge on best practices for infant and child nutrition, we investigate whether these activities are transforming societal gender norms. While evidence shows an improved understanding and awareness of gender-positive roles by both men and women, restrictive gender norms remain prevalent, including among lead volunteers. We suggest the possibility of longer term shifts in power dynamics in the home and society at large as well as suggest how humanitarian response can better integrate gender transformative programming.